Role of JAK3 in the Pathogenesis of Oxidative Stress-Induced Kidney Fibrosis (Journal of Renal and Hepatic Disorders, 2018)
The Janus kinase (JAK) tyrosine kinase family and JAK/STAT signal transduction pathway may act in kidney fibrogenesis. JAK3 expression was investigated in in vitro and in vivo models of kidney fibrosis involving oxidative stress. There was a marked down-regulation of JAK3 mRNA in rat kidney tubular epithelial cells (NRK52E) and fibroblasts (NRK49F) exposed to 1.0 mM H2O2 for 18–20 h compared with controls, which correlated with increased apoptosis and decreased mitosis in both cell lines. However, JAK3 protein levels were not significantly different in control and H2O2-treated epithelial and fibroblast cultures. JAK3 activation (phospho-tyrosine) increased in NRK52E cells and decreased in NRK49F cells with oxidative stress. STAT3 phosphorylation decreased in both cell lines with oxidative stress compared with controls. JAK3 protein expression and localisation were investigated in kidneys using the unilateral ureteral obstruction (UUO) model (0–7 days, rats) of kidney fibrosis that involves oxidative stress. JAK3 protein expression did not differ between UUO and controls; however, JAK3 localisation increased temporally with UUO, with strong epithelial expression in mitotic cells compared with controls. Apoptotic tubular epithelium showed minimal JAK3. In summary, in vitro, decreased kidney JAK3 mRNA after oxidative stress was not seen translationally. Differences in the activation of the JAK3/STAT3 pathway may have different consequences for renal fibrosis. In vivo, changes in JAK3 protein localisation, and especially its colocalisation with mitotic cells, indicate that JAK3 protein may contribute to renal tubular epithelial cell proliferation after oxidative stress.
Keywords: JAK3; Janus kinase tyrosine kinase family; kidney fibrosis; oxidative stress; STAT